PHILOSOPHICAL COMPREHENTION OF THE PROBLEM OF TERRORISM - Фоменко, А. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article deals with the analysis of philosophical concepts towards comprehending the nature of terrorism in the newest global reality